2021
DOI: 10.1007/s10443-020-09854-y
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Improvement of Thermoplastics-Based Composites by Atmospheric Plasma and UV Treatments

Abstract: The present work is concerned with adhesive bonding of thermoplastic composites used in general aerospace applications, including polyphenylene sulfide (PPS), polyetherimide (PEI) and polyetheretherketone (PEEK) carbon fibre composites. Three different surface treatments have been applied to the PEEK, PPS and PEI-based composites in order to enhance the adhesion: atmospheric plasma, ultraviolet radiation (UV) and isopropanol wiping as a control. Water contact angles and free surface energies were measured foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…8 In this regard, thermoplastic composites (TPCs) possess a great potential with superior mechanical strength, 9 formability, 10 and fabrication advantages. 11…”
Section: Introductionmentioning
confidence: 99%
“…8 In this regard, thermoplastic composites (TPCs) possess a great potential with superior mechanical strength, 9 formability, 10 and fabrication advantages. 11…”
Section: Introductionmentioning
confidence: 99%
“…These results are in good agreement with the previous literature reports. For example, Scarcelli et al 6 reported θ water = 95 , Luo et al 42 reported θ water = 96 , and we measured 96 ± 1 W contact angle for the PPS surface. Similarly, Wang et al 9 reported θ glycerol = 80 ± 2.1 , and we found 80 ± 2 GLY contact angle in our experiments.…”
Section: Wettability Properties and Surface Free Energy Analysis Of Ppsmentioning
confidence: 56%
“…For example, Scarselli et al treated the PPS surface with atmospheric plasma and UV lamp to increase the SFE of the PPS, and obtained improved lap shear strength properties as a result of this treatment. 6 Lv et al obtained a corrosionresistance superhydrophobic PPS surface by introducing the silicone rubber particles and carbon nanotubes into PPS matrix. 7 The same group converted the PPS surface to a superhydrophobic surface using amino silicon oil as a low SFE material.…”
Section: Introductionmentioning
confidence: 99%
“…The increased roughness can be easily obtained at a reduced cost by mechanical abrasion (grinding, sanding, or sandblasting) but may be relatively ineffective and hard to control. [ 3,4 ] Chemical methods are also described, such as acid etching, [ 5 ] but they are sometimes accompanied with an alteration of the physicochemistry of the surface and the etching in solution requires the use of solvents that are themselves toxic and sometimes volatile (volatile organic compound).…”
Section: Introductionmentioning
confidence: 99%